Cultural Expertise: An Emergent Concept and Evolving Practices - Holden, Livia (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
Cultural expertise in the form of expert opinions formulated by social scientists appointed as experts in the legal process is not different from any other kind of expertise in court. In specialised fields of law, such as native land titles in America and in Australia, the appointment of social scientists as experts in court is a consolidated practice. This Special Issue focuses on the contemporary evolution and variation of cultural expertise as an emergent concept providing a conceptual umbrella for a variety of evolving practices, which all include use of the specialised knowledge of social sciences for the resolution of conflicts. It surveys the application of cultural expertise in the legal process with an unprecedented span of fields ranging from criminology and ethnopsychiatry to the recognition of the rights of autochthone minorities including linguistic expertise, and modern reformulation of cultural rights. In this Special Issue, the emphasis is on the development and change of culture-related expert witnessing over recent times, culture-related adjudication, and resolution of disputes, criminal litigation, and other kinds of court and out-of-court procedures. This Special Issue offers descriptions of judicial practices involving experts in local laws and customs and surveys of the most frequent fields of expert witnessing that are related with culture; interrogates who the experts are, their links with local communities, and also with the courts and the state power and politics; how cultural expert witnessing has been received by judges; how cultural expertise has developed across the sister disciplines of history and psychiatry; and eventually, it asks whether academic truth and legal truth are commensurable across time and space.